2010
DOI: 10.1002/jbt.20333
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiling of mRNA expression of glutathione S‐transferase superfamily genes in various tissues of bighead carp (Aristichthys nobilis)

Abstract: ABSTRACT:The expression of glutathione S-transferase (GST) is a crucial factor in determining the sensitivity of cells and organs in response to a variety of toxicants. In this study, we cloned the core nucleotide of alpha, kappa, mu, mGST, pi, rho, and theta-like GST genes from bighead carp (Aristichthys nobilis). Their derived amino acid sequences were clustered with other vertebrate GSTs in a phylogenetic tree, and the bighead carp GST sequences have the highest similarity with those from common carp and ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Interestingly, the molecular expression of GST may be considered as a biomarker for xenobiotics exposure [72][73][74]. Many toxicologists expect that the highest level of GST expression may occur in the liver where metabolism mostly occurs [75]. In this study, the mRNA expression of GST in the liver of NaF-exposed fish showed a significant reduction compared to control fish.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, the molecular expression of GST may be considered as a biomarker for xenobiotics exposure [72][73][74]. Many toxicologists expect that the highest level of GST expression may occur in the liver where metabolism mostly occurs [75]. In this study, the mRNA expression of GST in the liver of NaF-exposed fish showed a significant reduction compared to control fish.…”
Section: Discussionmentioning
confidence: 59%
“…Our results also showed varied trends of the same gene in different fish. The possible explanations for the observed variations could be attributed to (1) the vulnerability to MG among different fish species was quite different (Steffens et al,1961; Alderman and Clifton‐Hadley,1993); and (2) that the constitutive mRNA expression of the same detoxification‐related was diverse in different fish species (Li et al,2010) which leads to the different detoxified ability. In this study, the constitutive mRNA expression level of CYP1A, GSTR, GSTA, GPX, UCP2, or HSP70 genes in the liver of Nile tilapia and other major Chinese freshwater fishes have been analyzed by semiquantitative PCR after MG exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis revealed that these two zebrafish GSTs contain sequences corresponding to the glutathione‐binding site (G‐site) and substrate‐binding site (H‐site) that are involved in the glutathione conjugation reaction . In fish such as zebrafish and bighead carp, GST Pi‐1 (GSTP1) is highly expressed in the liver, kidney, gills, and intestine, implying a role of this enzyme in detoxification . In humans, in addition to its role in detoxification, genetic polymorphisms of GSTP1 have been linked to prostate, testicular, and bladder cancer .…”
Section: Introductionmentioning
confidence: 99%
“…[26,30,31] In fish such as zebrafish and bighead carp, GST Pi-1 (GSTP1) is highly expressed in the liver, kidney, gills, and intestine, implying a role of this enzyme in detoxification. [12,32] In humans, in addition to its role in detoxification,…”
mentioning
confidence: 99%